2011
DOI: 10.22364/mhd.47.3.3
|View full text |Cite
|
Sign up to set email alerts
|

MHD flow and heat transfer near the stagnation point on a stretching/shrinking sheet in a micropolar fluid

Abstract: The problem of two-dimensional magnetohydrodynamic (MHD) stagnation point flow of an incompressible micropolar fluid over a stretching/shrinking sheet is studied. The governing continuity, momentum, angular momentum and heat equations together with the associated boundary conditions are transformed into a system of ordinary differential equations using a similarity transformation. This system is then solved numerically by a finite difference method. The effects of the magnetic parameter, material parameter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zaimi and Ishak [13] found that dual solutions exist in a certain range of buoyancy parameters. Dual solutions for a certain range of shrinking parameter also reported in the study by Bachok et al, [14,15]. Later, Mukhopadhyay [16] described the boundary layer flow and heat transfer towards a porous exponential stretching sheet in the presence of magnetic field.…”
Section: Introductionmentioning
confidence: 53%
“…Zaimi and Ishak [13] found that dual solutions exist in a certain range of buoyancy parameters. Dual solutions for a certain range of shrinking parameter also reported in the study by Bachok et al, [14,15]. Later, Mukhopadhyay [16] described the boundary layer flow and heat transfer towards a porous exponential stretching sheet in the presence of magnetic field.…”
Section: Introductionmentioning
confidence: 53%